Dispersion of Boron Nitride Nanotubes by Pluronic Triblock Copolymer in Aqueous Solution - Jeon, Sang-Woo (Polymers (Basel), 2019)
Boron nitride nanotubes (BNNTs) have been of interest for their excellent thermal, electrical, and mechanical properties, and they have a broad spectrum of potential applications, such as in piezoelectric materials, reinforcement of materials, and electrothermal insulation materials. For practical use of BNNTs, it is desirable to disperse them in aqueous solution, which improves convenience of handling. However, it is still difficult to make a homogenous and stable BNNT dispersion in aqueous solution, due to their strong van der Waals interactions and hydrophobic surface. To solve these problems, we used Pluronic P85 and F127, which have both hydrophilic groups and hydrophobic groups. Here, we report the wrapped structure of a Pluronic polymer-BNNT dispersion by using small-angle neutron scattering, UV–Vis spectroscopy, thermogravimetric analysis, and atomic force microscopy.